Penggunaan Metode Keterampilan Proses untuk Meningkatkan Aktivitas dan Hasil Belajar Bahasa Indonesia melalui Telepon Siswa Kelas IV SD Negeri 02 Kundur - Usman, Raja (GERAM, 2018)
The purpose of this study is to improve the activity and learning outcomes of fourth grade students of State Elementary School 03 Kundur because in reality there are a few students who get the lowest score that is 62 while the Criterion of Minimal Completeness(KKM) of his school has set 70. The Efforts to improve learning outcomes is by using the Process Skill Approach consisting of two cycles in which Cycle I and Cycle II. The Subject in this study is  students of grade IV of State Elementary School 02 Kundur. This type of research is Classroom Action Research. The result of this study is from the beginning until two cycles that is pra-cycle on the average score 74.44, cycle I that is 74.11, and cycle II increased to 80.44. The score of cycle I is the lowest 65 and the highest  85. In the cycle II, lowest score is 70 and the highest one is 90. The complete score in cycle I is only 19 students (70,37) and uncomplete score is 8 students (29,63%). In cycle II, there is a change in which all students have completed score (100%). Having been viewed from the range of score ​​and criteria on the high cycle I score is (26.93%), sufficient score is 44.44% and low score is 29.63%. so cycle I of criteria score lies in sufficient Criteria score . On the second cycle, there are increases of the  very high criteria score 11.11%, high score criteria 48.15% and sufficient score criteria 40.74% then the score of cycle II lies in the High score criteria. The Subject in this study is  students of grade IV State Elementary School 03 Kundur.